Investigation of the influence of turbulence to tribological performance on smooth and multistep journal bearing with hydrodynamics simulation - Muchammad, M.; Wibowo, Daniel Dwi Putra; Tauviqirrahman, Mohammad; Setiyana, Budi; Yohana, Eflita; Jamari, J. (Frontiers in Mechanical Engineering, 2022)
Bearing is an element that maintains the relative motion between two components in industrial machines, while journal bearing is often used to keep the shaft constantly rotating on its axis. Generally, an increase in journal bearing’s performance is essential for industrial development. An increase in engine speed affects the distribution of pressure, temperature, and acoustics. Scientists have proposed various methods to analyze pressure distribution, load-bearing capacity, acoustic power, friction force, cavitation, and elastic phenomena to improve journal bearings' tribological performance. Therefore, this study aimed to discuss the differences in the flow type modeling between smooth and multistep journal bearings. The results indicated that tribological performance increased significantly in turbulent flow in smooth and multistep journal bearing. The simulation results showed a difference between k-epsilon turbulent flow modeling and k-omega flow modeling.